2005
DOI: 10.1063/1.2084737
|View full text |Cite
|
Sign up to set email alerts
|

Time to completion reveals problem-solving transfer

Abstract: Abstract. Two equally skilled groups of students taking introductory mechanics solve related physics problem pairs in reverse order with respect to each other, using the web-based Socratic tutor, MasteringPhysics. In tutorial problems containing help in the form of requestable hints, descriptive text, and feedback, twice as many students were able to complete problems correctly in real-time compared to problems that did not provide any help (end-of-chapter problems). The prepared group in a given related pair … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…However, research on knowledge transfer in this environment shows that students need 15.4% fewer hints and submit 11.4% fewer wrong answers when working a subsequent problem on the same topics as the previous one. 12,13 We estimate that this would be consistent with a learning effect of the increased student skill by about 0.5 standard deviation ͑but just on items concerning that detailed topic͒.…”
Section: Resultsmentioning
confidence: 58%
“…However, research on knowledge transfer in this environment shows that students need 15.4% fewer hints and submit 11.4% fewer wrong answers when working a subsequent problem on the same topics as the previous one. 12,13 We estimate that this would be consistent with a learning effect of the increased student skill by about 0.5 standard deviation ͑but just on items concerning that detailed topic͒.…”
Section: Resultsmentioning
confidence: 58%
“…Previous research has shown that three distinctive groups of students consistently emerge when the problem completion rate is plotted against the logarithmic problem completion time (Warnakulasooriya, Palazzo, & Pritchard, 2006;Warnakulasooriya, Palazzo, & Pritchard, 2007;Warnakulasooriya & Pritchard, 2005). The first group of students, called quick responders, is able to finish the problem within~2.5 minutes without using any hints or submitting any incorrect answers.…”
Section: Methodsmentioning
confidence: 99%